NUP98‐NSD1 fusion in association with FLT3‐ITD mutation identifies a prognostically relevant subgroup of pediatric acute myeloid leukemia patients suitable for monitoring by real time quantitative PCR. Issue 11 (2nd September 2013) - Akiki, Susanna; Dyer, Sara A.; Grimwade, David; Ivey, Adam; Abou‐Zeid, Nervana; Borrow, Julian; Jeffries, Sally; Caddick, Judith; Newell, Hayley; Begum, Suriya; Tawana, Kiran; Mason, Joanne; et al.
<x xml:space="preserve">Abstract</x> The cytogenetically cryptic t(5;11)(q35;p15) leading to the NUP98‐NSD1 fusion is a rare but recurrent gene rearrangement recently reported to identify a group of young AML patients with poor prognosis. We used reverse transcription polymerase chain reaction (PCR) to screen retrospectively diagnostic samples from 54 unselected pediatric AML patients and designed a real time quantitative PCR assay to track individual patient response to treatment. Four positive cases (7%) were identified; three arising de novo and one therapy related AML. All had intermediate risk cytogenetic markers and a concurrent FLT3‐ITD but lacked NPM1 and CEBPA mutations. The patients had a poor response to therapy and all proceeded to hematopoietic stem cell transplant. These data lend support to the adoption of screening for NUP98‐NSD1 in pediatric AML without otherwise favorable genetic markers. The role of quantitative PCR is also highlighted as a potential tool for managing NUP98‐NSD1 positive patients post‐treatment. © 2013 Wiley Periodicals, Inc.